2018
DOI: 10.29332/ijhs.v2n2.110
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile in obese children with and without insulin resistance

Abstract: Obesity is increasing nowadays including in children and there is lack of information on the pathophysiology and their complication such as insulin resistance and dyslipidemia. This study was aimed to investigate the comparison of lipid profile in obese children with and without insulin resistance. A crossectional study held at an elementary school in Denpasar, Bali from August until September 2015. Independent t-test, Mann-Whitney test, and Multivariate analysis of covariance (MANCOVA) were performed to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…21 improvement of pediatric nutritional support care according to the underlying diseases is the reason why the hospital malnutrition in our hospital can be decreased. [19] Our study found that severe or moderate acute malnutrition according to weight-for-height less than 3 or 2 SD of WHO growth standard at admission associated with high risk for malnutrition based on STRONGkids score classification. Children with severe acute malnutrition at admission have 10.9 times more high-risk classification on STRONGkids compare with well nourishes children.…”
Section: Results and Analysismentioning
confidence: 51%
“…21 improvement of pediatric nutritional support care according to the underlying diseases is the reason why the hospital malnutrition in our hospital can be decreased. [19] Our study found that severe or moderate acute malnutrition according to weight-for-height less than 3 or 2 SD of WHO growth standard at admission associated with high risk for malnutrition based on STRONGkids score classification. Children with severe acute malnutrition at admission have 10.9 times more high-risk classification on STRONGkids compare with well nourishes children.…”
Section: Results and Analysismentioning
confidence: 51%
“…Treatment outcomes were assessed according to the achievement of anatomical and functional outcomes. Dysfunction of the gluteal muscles due to the high position of the greater trochanter, taking into account its pathogenesis and the patient's age, we propose to correct simultaneously with the direction of the position of the cervical deformity in the intertrochanteric region in order to deviate the greater trochanter posteriorly (Verrall et al, 2007;Stagni et al, 2000;Tjiang & Sidiartha, 2018). A decrease in the distance between the greater trochanter of the femur, the cartilaginous edge of the acetabulum, and the ilium leads to their mechanical conflict, first during abduction and extension of the thigh, and in severe cases, in the middle position.…”
Section: Resultsmentioning
confidence: 99%
“…In this order of ideas, sensory stimulation favors learning, as highlighted below: Life in relation to the world that surrounds the child begins through the senses and feelings begins your mind to build your own ideas; therefore, from the beginning, it is necessary to guide the interpretation of sensory impressions, in the clarification of sensitive perceptions. Sensory stimulation is given thanks to the union of perception and the senses thus creating a way for learning (Soler, 1992;Tjiang et al, 2018). Giler, R. D. G., Zambrano, T. Y. M., Anzules, F. E. V., & Burgos, V. D. P. Z.…”
Section: Resultsmentioning
confidence: 99%